High-moisture acid-treated milo for swine - G L Allee; Jack G Riley; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Two trials involving 105 finishing pigs (initial average weight 125 pounds) and 55 growing pigs (initial average weight 28 pounds) were conducted to determine the nutritional value of high-moisture, acid-treated milo in swine rations. Additionally, feeding method (complete mixed or free-choice) and processing method (ground or whole) were compared. The high-moisture milo (22% moisture) was treated with either propionic acid (P.A.) 0.6% w/w, or ammonium isobutyrate (AIB) 1.75% w/w. Pigs fed high-moisture, acid-treated milo as a complete mixed ration gained at the same rate and were just as efficient in feed utilization as pigs fed the dry, complete mixed ration. In both trials, both acid treatments gave similar pig performances. In the finishing trial, pigs fed high-moisture, acid-treated milo and supplement free-choice gained at the same rate and were just as efficient in feed utilization as pigs fed the complete mixed rations. However, with growing pigs, free-choice feeding significantly (P<.05) reduced daily gain. Finishing pigs fed whole high-moisture, acid-treated milo required significantly (P<.05) more feed per unit of gain than pigs fed the ground high-moisture acid-treated milo. Whole high-moisture, acid-treated milo was used as efficiently as ground high-moisture, acid-treated milo by young pigs. Acid-treated, high-moisture milo is equal to dry milo in feeding value when the acid-treated milo is fed in a ground complete mixed ration. With free-choice feeding, pigs fed high-moisture, acid-treated milo may not eat enough supplement to give maximum performance.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Acid-treated; Milo; Feeding methods